An incidental peri-adrenal cystic lesion. (1st August 2012) - Powell, George; Burrows, Cerys; Houghton, Andrew; Otter, Mark
Abstract : A 50-year-old man was found to have an incidental peri-adrenal cystic lesion on CT imaging which was removed laparoscopically. Histological examination showed a cystic structure composed of respiratory and cuboidal-type epithelium with underlying smooth muscle, cartilage and seromucinous glands. The differential diagnosis for such a lesion includes bronchogenic cyst or teratoma differentiated. This case report offers an overview of both the conditions and the difficulties encountered in the histological distinction.